Rare coexistence of hypopituitarism with osteogenesis imperfecta – A double-trouble for bone - Rajdeep Basu; Soumik Goswami; Nilanjan Sengupta; Arjun Baidya; Sunetra Mondal; Kumar Swapnil; Rajat Deb; Vibhu Ranjan Khare; Joydip Datta (Bone Reports, 2024)
Osteogenesis imperfecta (OI) commonly involving defects in COL1A1 and COL1A2 is a rare hereditary disease of bone fragility affecting 6–7 per 100,000 population. On the other hand, hypopituitarism is a separate entity that manifests with reduced levels of pituitary hormones. The cooccurrence of these two is seldom reported previously in literature as a deviation from Occam's razor. Here, we reported a case of pathological fracture in a 31-year-old male who had blue sclera and secondary adrenal insufficiency, hypogonadotropic hypogonadism, and growth hormone deficiency along with primary autoimmune hypothyroidism. Diagnosis of OI was suggested by heterozygous missense variant in exon 40 of the COL1A2 gene (chr7: g.94423092G > A; Depth: 99×) that resulted in the amino acid substitution of Serine for Glycine at codon 847. Replacement of glucocorticoid, levothyroxine, and testosterone was started along with antiresorptive therapy for better bone health outcomes.